2021
DOI: 10.1186/s12940-021-00707-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term exposure to particulate air pollution on heart rate variability in normal-weight and obese adults

Abstract: Background The adverse effects of particulate air pollution on heart rate variability (HRV) have been reported. However, it remains unclear whether they differ by the weight status as well as between wake and sleep. Methods A repeated-measure study was conducted in 97 young adults in Beijing, China, and they were classified by body mass index (BMI) as normal-weight (BMI, 18.5–24.0 kg/m2) and obese (BMI ≥ 28.0 kg/m2) groups. Personal exposures to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Our study found that acute BC exposure was primarily associated with increased risks of ST-segment depression events. Similar to the present study, increased risk of ST-segment depression associated with acute BC exposure has been observed in two studies in the United States. , For HR and HRV variables, several studies in China showed that short-term BC exposure was associated with increased HR, declined SDNN , and LF, which are consistent with our results. We compared results from two studies (repeated-measure study and panel study), and the consistent results between these two studies highlight the robustness of the novel findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that acute BC exposure was primarily associated with increased risks of ST-segment depression events. Similar to the present study, increased risk of ST-segment depression associated with acute BC exposure has been observed in two studies in the United States. , For HR and HRV variables, several studies in China showed that short-term BC exposure was associated with increased HR, declined SDNN , and LF, which are consistent with our results. We compared results from two studies (repeated-measure study and panel study), and the consistent results between these two studies highlight the robustness of the novel findings.…”
Section: Discussionsupporting
confidence: 92%
“…Then, the uptake of these toxic chemical species by the alveolar epithelium enters the bloodstream [13]. In fact, cardiovascular diseases and carcinogenesis, such as elevated systolic blood pressure, heart rate variability, and respiratory infections, have been confirmed to be partially associated with BC contamination [14][15][16]. The exposure to persistent BC tends to induce augmented premature mortalities and abated lung function [17][18][19].…”
Section: Introductionmentioning
confidence: 99%